Waves in the Communication Flow. The Interplay of Constitution, Legislative, and Governmental Institutions in Mass Media - Haase, Fee-alexandra (Nómadas. Critical Journal of Social and Juridical Sciences, 2007)
This article compares in case studies regarding the constitution, written laws, and other national institutions the influence of the state regarding the production and function of mass communication and related values in different countries. Our interest is to demonstrate the differences between countries under the aspects of a) national constitution and governmental institutions that provide or not provide guidelines in terms of the use and protection of communication; b) national organisations that provide additonal guidelines; c) international organisations for the use of mass communication media in a country. The interplay of national constitution, legislative body, and governmental institutions is the framework for the existence of national mass communication. Under the title “Waves in The Communication Flow“ we will face this framework of exterior institutions for different national states regarding their influence on mass communication. As mass communication we can define all institutions producing information for a wide audience delivered in mass media. As a process we can define mass communication as a ‘flow of any information’ delivered by mass media. This flow can be promoted or prohibited by the framework of institutions named above. This article examines the forms, extent, and nature of the use of laws and constitutional systems with an interest in the methodology of comparative studies in constitutional law.